2017
DOI: 10.1002/jsfa.8425
|View full text |Cite
|
Sign up to set email alerts
|

Proximate composition, amino acid and fatty acid profiles of marine snail Rapana venosa meat, visceral mass and operculum

Abstract: The operculum of Rv may became a very interesting source for some protein and flavor peptide development, and the edible parts of Rv may be utilized for special dietary applications requiring high amounts of taurine, EPA, DHA and a lower ω6/ω3 fatty acid ratio. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…Amino acid contents in rabbit meat were determined according to the method of Luo et al (2017) with minor modifications. Rabbit meat samples were hydrolysed with 10 mL of 6 mol L À1 hydrochloric acid (HCl) in a vacuum at 110 C for 24 h. The hydrolysates were taken out of the oven, cooled down, and then diluted with ultrapure water in a 50-mL volumetric flask.…”
Section: Amino Acid Profile Analysismentioning
confidence: 99%
“…Amino acid contents in rabbit meat were determined according to the method of Luo et al (2017) with minor modifications. Rabbit meat samples were hydrolysed with 10 mL of 6 mol L À1 hydrochloric acid (HCl) in a vacuum at 110 C for 24 h. The hydrolysates were taken out of the oven, cooled down, and then diluted with ultrapure water in a 50-mL volumetric flask.…”
Section: Amino Acid Profile Analysismentioning
confidence: 99%
“…Raw materials used in feeds are expected not only to be a source of protein that provides better growth, but they are also expected to provide features such as enhanced reproduction, disease protection, environmental stress resistance, better coloration and delicious meat. In this regard, it has been previously reported by Luo, et al [69] that the hemocyanin and its functional units from veined Rapa whelk showed phenol oxidase activity [70,71], antimicrobial activity [70,72], antiviral activity [73], antitumor activity [74,75] and healing properties on skin burns [76].…”
Section: Resultsmentioning
confidence: 99%
“…Studies have confirmed that a low ration of ω6/ω3 PUFA is essential to help prevent inflammatory diseases, cancer, cardiovascular diseases and other chronic diseases (Yu et al, 2015;Yang et al, 2016;Luo et al, 2017; reviewed by Saini & Keum, 2018), while a TA B L E 2 Comparison of the content (g/100 g wet weight) and composition of amino acids in different prawn and shrimp species Ec, E. carinicauda; Em, E. modestus; Es, E. superb; Lv, L. vannamei; Me, M. ensis; Mn, M. nipponense; Pc, P. clarkia; Pj, P. japonicas; Pk, P. high dietary ratio of ω6/ω3 PUFA may increase the risk of prostate cancer among white men, risk of high-grade prostate cancer among all men and risk of obesity of newborn in later life (Vaidya & Cheema, 2017;Williams et al, 2011). In the present study, the ω6/ω3 fatty acid ratios in muscle of wild-typed prawn and the new variety was 0.13 and 0.09, which was the lowest value compared with the reported shrimp species.…”
Section: Discussionmentioning
confidence: 98%
“…After complete drying, the residue was diluted in sodium citrate buffer (pH 2.2) and analysed by an L‐8900 amino acid analyser (Hitachi). The amino acids were identified and quantified based on the standard curves constructed with a mixture of commercially available standards (Luo, Xing, Wang, Peng, & Li, ). All the amino acid standard, including lysine (Lys), methionine (Met), threonine (Thr), isoleucine (Ile), leucine (Leu), valine (Val), phenylalanine (Phe), histidine (His), aspartic acid (Asp), serine (Ser), glutamic acid (Glu), glycine (Gly), alanine (Ala), cysteine (Cys), tyrosine (Tyr), arginine (Arg) and proline (Pro), were purchased from Sigma‐Aldrich.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation